DARI GEMEINSCHAFT KE DIGITAL-GESELLSCHAFT: DIALEKTIKA INTERAKSI GURU-MURID DI MADRASAH ERA POST-PANDEMI - Huda, Samsul; Fitriani, Intan; Zahro, Rofiatus; Nurwahid, Nurwahid; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This article examines the fundamental impact of digital technology adoption, particularly e-learning platforms and WhatsApp, on teacher–student interaction patterns in madrasahs. The scope of the study focuses on the transformation of pedagogical relationships within Islamic educational settings. Adopting the perspective of the Sociology of Ereignis, this research conceptualizes interaction not merely as an exchange of information, but as a meaningful educational event that is increasingly mediated—and potentially reduced—by digital screens. The study employs a qualitative approach through a systematic literature review, critically analyzed using sociological and philosophical frameworks. The findings indicate an ontological shift from warm, relational, and spiritually grounded interactions (Gemeinschaft) toward more functional, instrumental, and distanced forms of interaction (Digital-Gesellschaft). Furthermore, the study reveals a dialectical paradox of digital technology: while it democratizes access to knowledge and weakens traditional hierarchical structures, it simultaneously risks diminishing the spiritual depth of teacher–student relationships and exacerbating social inequalities through the digital divide. The article concludes that, in order to preserve the essence of Islamic education grounded in ta’dib and tarbiyah, madrasahs must move beyond mere technological adoption and critically reconstruct digital interactions so that they remain authentic educational encounters rather than mere transactions of information.